2017
DOI: 10.1159/000479795
|View full text |Cite
|
Sign up to set email alerts
|

The Histopathological Characteristics Caused by <b><i>Trionyx sinensis</i></b> Hemorrhagic Syndrome Virus (TSHSV) and Comparative Proteomic Analysis of Liver Tissue in TSHSV-Infected Chinese Soft-Shelled Turtles (<b><i>Pelodiscus sinensis</i></b>)

Abstract: Trionyx sinensis hemorrhagic syndrome virus (TSHSV) is a pathogen that causes severe hemorrhagic syndrome and irreversible damage to different infected tissues of Pelodis cus sinensis, ending in the death of affected organisms. In the present study, the histopathological characteristics of TSHSV-infected P. sinensis were analyzed and compared by HE staining. Relative and absolute quantification (iTRAQ)-based proteomic analysis was employed to explore the molecular pathology of liver injury. Anatomical features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
1
9
0
2
Order By: Relevance
“…Consequently, the disease risk that reptile nidoviruses pose to wild populations of reptiles is largely unknown. Worldwide the number of reptile species listed as threatened continues to increase (24) and emerging or reemerging infectious diseases including various fungi (25)(26)(27), bacteria (28) and viruses (29)(30)(31) are cause for concern. Infectious disease is rarely a single contributing factor in known plant and animal extinctions, with the exception being amphibian panzootics caused by chytrid fungus (Batrachochytrium dendrobatidis) (32)(33)(34), yet understanding the risk they pose may be critical in preventing ongoing population declines.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the disease risk that reptile nidoviruses pose to wild populations of reptiles is largely unknown. Worldwide the number of reptile species listed as threatened continues to increase (24) and emerging or reemerging infectious diseases including various fungi (25)(26)(27), bacteria (28) and viruses (29)(30)(31) are cause for concern. Infectious disease is rarely a single contributing factor in known plant and animal extinctions, with the exception being amphibian panzootics caused by chytrid fungus (Batrachochytrium dendrobatidis) (32)(33)(34), yet understanding the risk they pose may be critical in preventing ongoing population declines.…”
Section: Introductionmentioning
confidence: 99%
“…A concentração utilizada neste estudo não ocasionou toxicidade em O. niloticus, embora, alguns estudos demonstram que este agente biológico pode alterar funções biológicas importantes dos vertebrados (Shaban et al, 2003;Chen et al, 2014;Mariano et al, 2019). No entanto, é necessário considerar a influência da forma de exposição do organismo ao agente, seja às protoxinas, às toxinas ativas, à bactéria ou aos esporos.…”
Section: Discussionunclassified
“…De acordo com Villaverde et al (2014), alguns biopesticidas à base de Bt possuem um espectro relativamente amplo de organismos alvo. Ainda, alguns estudos apontam o Bt como agente nocivo a organismos não alvos como tartarugas (Chen et al, 2014) e peixes (Omoya & Akharaiyi, 2015;Mariano et al, 2019).…”
Section: Introductionunclassified
“…When compared with previously discovered T. sinensis viruses, TSHSV appears to be more virulent, causing high mortality both in the wild and in captivity [5]. TSHSVinfected turtles display typical characteristics, namely breathing difficulty, interstitial pneumonia, and hyperemic laryngeal mucosa in the throat [13,14]. An artificial infection experiment has demonstrated that TSHSV-infected turtles are seriously hemorrhagic in multiple organs, including liver, kidney and intestine [13].…”
Section: Introductionmentioning
confidence: 99%